1998
DOI: 10.1159/000028031
|View full text |Cite
|
Sign up to set email alerts
|

Human Psoriatic Skin in Organ Culture: Comparison with Normal Skin Exposed to Exogenous Growth Factors and Effects of an Antibody to the EGF Receptor

Abstract: Organ cultures were established from psoriatic lesional skin of 24 different individuals and maintained for 8 days under serum-free, growth-factor-free conditions. Nonlesional skin from 14 of the same individuals and normal skin from another 12 individuals were also maintained in organ culture. At the end of the incubation period, the tissues were fixed in formalin and examined histologically. Lesional skin continued to express features of psoriatic plaque, which included irregularly shaped epithelial cells ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 28 publications
(34 reference statements)
4
33
0
Order By: Relevance
“…A number of approaches have led to the conclusion that the triggering event in psoriasis is an immune system defect (Valdimarsson et al, 1995;Austin et al, 1999). Nevertheless, the downstream events that precipitate psoriatic hyperplasia (like those in retinoid hyperplasia), involve keratinocyte growth regulation (Gottlieb et al, 1988;Elder et al, 1989;Cook et al, 1992;Piepkorn et al, 1998Piepkorn et al, , 2003Varani et al, 1998). Utility of agents that target abnormal keratinocyte proliferation for treatment of hyperplastic skin diseases will, ultimately, require formulation for topical delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of approaches have led to the conclusion that the triggering event in psoriasis is an immune system defect (Valdimarsson et al, 1995;Austin et al, 1999). Nevertheless, the downstream events that precipitate psoriatic hyperplasia (like those in retinoid hyperplasia), involve keratinocyte growth regulation (Gottlieb et al, 1988;Elder et al, 1989;Cook et al, 1992;Piepkorn et al, 1998Piepkorn et al, , 2003Varani et al, 1998). Utility of agents that target abnormal keratinocyte proliferation for treatment of hyperplastic skin diseases will, ultimately, require formulation for topical delivery.…”
Section: Discussionmentioning
confidence: 99%
“…As a first step, we used a model of retinoidinduced epidermal hyperplasia in human skin organ culture as the test system. Past studies have demonstrated that although the etiologies are different, retinoid hyperplasia (Varani et al, 2001), like the hyperplasia in psoriasis (Gottlieb et al, 1988;Elder et al, 1989;Cook et al, 1992;Piepkorn et al, 1998Piepkorn et al, , 2003Varani et al, 1998), involves intraepidermal production of ligands for the epidermal growth factor (EGF) receptor, and autocrine or paracrine EGF receptor activation. The results presented here demonstrate significant reduction in retinoid-stimulated hyperplasia without detrimental effects on normal keratinocyte proliferation or fibroblast function.…”
mentioning
confidence: 99%
“…Consistent with this theory, we previously demonstrated that the same skin that becomes hyperplastic after transplantation onto SCID mice remains histologically normal when placed in organ culture in the absence of exogenous growth factors. Hyperplasia can be induced in organ-cultured skin by treatment with exogenous growth factors (Varani et al 1994(Varani et al , 1998.…”
Section: Zeigler Et Almentioning
confidence: 99%
“…No animal disease completely mimics psoriasis (Carroll et al, 1995;Sundberg et al, 1990). Keratinocytes and fibroblasts from psoriatic skin were isolated and studied in monolayer culture (Nickoloff et al 1989;Pellegrini et al, 1992;Priestley, 1987), and psoriatic lesional skin was studied in organ culture (Caron, 1968;Kondo, 1986;Kondo et al, 1992;Mils et al, 1994;Varani et al, 1998). Although some of the phenotypic characteristics of psoriatic lesional skin are maintained under in vitro culture conditions, other characteristics are lost over time (Kondo, 1986;Mils et al, 1994;Varani et al, 1998).…”
mentioning
confidence: 99%
“…Given that epidermal hyperplasia in retinoid-treated skin and psoriatic epidermal hyperplasia both involve increased keratinocyte proliferation driven by aberrant signaling through the epidermal growth factor receptor (EGF) receptor pathway (Gottlieb et al, 1988;Elder et al, 1989;Cook et al, 1992;Varani et al, 1998Varani et al, , 2001Piepkorn et al, 2003;Rittié et al, 2006), it was of interest to determine whether Bz-423 would reduce psoriatic keratinocyte hyperproliferation. To begin addressing this issue, we compared the effects of a topical formulation of Bz-423 with a potent topical steroid on human psoriatic skin transplanted onto severe, combined immunodeficient (scid) mice.…”
mentioning
confidence: 99%